AB0800 ESTABLISHMENT OF TECHNICAL PERFORMANCE CRITERIA AND REFERENCE INTERVALS FOR OSTEOARTHRITIS-RELATED SOLUBLE BIOMARKERS: THE APPROACH CONSORTIUM. (June 2019) - Bay-Jensen, Anne-Christine; Henrotin, Yves; Lindemann, Sven; Ladel, Christoph; Hick, Anne-Christine; Karsdal, Morten; Larkin, Jonathan; Struglics, André; Mobasheri, Ali
Abstract : Background: Disease modifying therapy of osteoarthritis (OA) represents an unmet clinical need, and appropriate outcome measures are required that can robustly identify patients with different OA phenotypes who may benefit from specific and more targeted therapies. APPROACH is an exploratory, 5-centre, 2-year prospective follow-up European cohort study. It entails extensive clinical, imaging, biomechanical and biochemical parameters, in a cohort recruited using machine learning models based on retrospective patient data to display a high likelihood of radiographic joint space width loss, MRI changes and/or knee pain over the course of the study. Biochemical markers (biomarkers) can be used to understand pathogenesis, drug mode of action and as prognostic tools, as well as finding the right treatment for the right patients. Objectives: Different biomarkers were selected to be measured in aPPROACH patient samples for prospective predictive and prognostic analyses. Here we describe the biological rational, reference ranges and technical performance of the selected biomarker. Methods: The aPPRAOCH cohort includes 300 OA patients recruited based on the aPPROACH enrichment model (www.approach.eu ), in the period from 2017 and 2019. Serum and urine will be collected at baseline, 6, 12 and 24 months, as well as pain, radiographic and MRI assessments. Results: Eighteen exploratory and technically validated biomarkers reflecting joint tissue (i.e. cartilage, bone, synovium) turnover were chosen based on following characteristics; i) has shown association with OA pathogenesis (published data such as OAI 1 ); ii) has shown diagnostic or prognostic potential 2 ; iii) GLP or GMP certified assay production with acceptable technical performance (e.g. precision and linearity data, table); iv) readily availability of the kits from consortium partner or from third party vendor. The markers will be tested asking following research questions: Can the markers alone or in combination subgroup patients into different phenotypes which display different progression rates, or with different pain and radiographic profiles. Also, we will test whether a change in markers are correlated with change in the clinical assessments scores. Results from these analyses may provide insight to the potential usage of the biomarkers in drug development. Conclusion: The aPPROACH consortium is the first European study that attempts to establish robust technical performance criteria and reference intervals for osteoarthritis-related soluble biomarkers in an effort to develop biomarker panels that can identify patients with different OA phenotypes. References: [1] Kraus VB et al. OAC 2015. 2) Bauer DC et al. OAC 2006. 3) Larsson S et al. OAC. 2014. 4) Wang SX et al. OAC 2017. 5) Bay-Jensen a-C et al. Drug Discov Today 2018. 6) He Y et al. OAC 2019. 7) Y. H, T. C, M. D, et al. OAC 2011. 8) Runhaar J et al. OAC Cartil. 2016. 9) Luo Yet al. Int J Mol Sci. 2018 Acknowledgement: This work has received support from the EU/EFPIA innovative Medicines initiative Joint Undertaking (APPROACH grant n° 115770). This communication reflects the views of the authors and neither IMI nor the European Union and EFPIA are liable for any use that may be made of the information contained herein. Disclosure of interests: Anne-Christine Bay-Jensen Shareholder of: I own shares of Nordic Bioscience, Employee of: I am a full-time employee in Nordic Bioscience, Yves Henrotin Shareholder of: artialis SA, Sven Lindemann Employee of: Employed by Merck KGaA, Christoph Ladel Employee of: Employee of Merck KGaA, Darmstadt, Germany, anne-Christine Hick Employee of: artialis SA, Morten Karsdal Shareholder of: I own shares of Nordic Bioscience, Employee of: I am a full-time employee in Nordic Bioscience, Jonathan Larkin Employee of: Employed by GSK, andré Struglics: None declared, ali Mobasheri: None declared